Immune Profile of Litopenaeus vannamei in Monoculture and IMTA Ponds System - Chrisna Adhi Suryono; Ervia Yudiati; Nuril Azhar (Jurnal Kelautan Tropis, 2023)
Integrated Multi Trophic Level (IMTA) is identified as the integrating culture of multi-species in one area. The effectiveness of space and feed is the main aspect from this point. The disease and health of shrimp management on shrimp production including immune boosters plays a critical aspect. The aim of this research is to determine and analyze the Litopenaeus vannamei immune system in different culture systems, namely polyculture (IMTA) and monoculture. Alginate was applied as supplementation diet by oral administration. The cellular and humoral immune parameters ie. Total hemolymph Count (THC), Phagocyte Activity (PA), Phagocyte Index (PI), Phenoloxidase activity (PO), and Superoxide dismutase activity (SOD) were assessed, monthly. A completely randomized design (CRD) with two treatments (IMTA and monoculture, and four replications in 500 m2 pond area was conducted. In the third month, THC and PA of shrimp from the monoculture pond resulted in significant differences (p<0.05) compared to polyculture (IMTA). SOD activity from monoculture is significantly higher (p<0.05) at every sampling period. In PO enzyme activity of shrimps from monoculture pond produced higher results compared to IMTA ponds in the 2nd and 3rd months. It is concluded that L. vannamei monoculture ponds produced higher immune parameters compared to IMTA ponds. The food competition in terms of feed and space from IMTA ponds may affect this fact. Improving the feeding technique is recommended.